2022
DOI: 10.3390/medicina58020158
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Non-invasive Scoring Systems in the Prediction of Esophageal Varices in Patients with Liver Cirrhosis—Single Center Experience

Abstract: Background and Objectives: Upper endoscopy is considered the gold standard for screening and diagnosis of esophageal varices (EV). Non-invasive methods for predicting EV have become a research hotspot in recent years. The aim of this study was to assess the role of non-invasive scores in predicting the presence of EV in patients with liver cirrhosis, and to determine the value of these scores in predicting the outcome of patients with cirrhosis presenting with acute variceal bleeding. Materials and Methods: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
7
1
Order By: Relevance
“…Notably, we found that the evaluation of small-intestinal mucosal injury using I-FABP levels had the best ability to discriminate the presence of GEV in patients with cirrhosis. Although there have been many reports on the diagnostic performance of LSM and various noninvasive scoring systems for GEV [19][20][21][22] , measuring I-FABP showed the best diagnostic performance and was superior to those in the present study. To the best of our knowledge, only one report has examined the relationship between GEV and I-FABP levels 23 .…”
Section: Discussioncontrasting
confidence: 69%
“…Notably, we found that the evaluation of small-intestinal mucosal injury using I-FABP levels had the best ability to discriminate the presence of GEV in patients with cirrhosis. Although there have been many reports on the diagnostic performance of LSM and various noninvasive scoring systems for GEV [19][20][21][22] , measuring I-FABP showed the best diagnostic performance and was superior to those in the present study. To the best of our knowledge, only one report has examined the relationship between GEV and I-FABP levels 23 .…”
Section: Discussioncontrasting
confidence: 69%
“…Our findings were also corroborated by the researchers revealing a strong correlation between MELD, ALBI, PALBI, AAR, and FIB-4 scores and the presence of EV. Specifically, the MELD score in the group of patients with EV was considerably higher than in the group of patients without EV 15 . Hsieh et al revealed that ALBI score was substantially connected with HVPG and other hemodynamic parameters, with a greater correlation coefficient compared to those of other fibrosis indicators, indicating that had a potentially crucial role 16 .…”
Section: Discussionmentioning
confidence: 80%
“…which are indicators of liver dysfunction 29 . This aligns with the results of El Sheref et al, who found that lower serum albumin levels and higher bilirubin levels (> 1.45mg/dl), along with higher haemoglobin levels (> 11.5g/dl), were predictors of variceal haemorrhage 30 However Glisic et al found signi cant increase in serum bilirubin in cirrhotic non variceal patients versus patients with varices and signi cant difference as regarding serum albumin in similar patients (2.9 mg/dl in variceal patients versus 2.7 mg/dl in non-variceal patients) 31 .…”
Section: Resultsmentioning
confidence: 99%